2021
DOI: 10.1097/j.jcrs.0000000000000614
|View full text |Cite
|
Sign up to set email alerts
|

Refractive and keratometric outcomes of supervised novice surgeon–performed limbal relaxing incisions: 1-year results

Abstract: LRIs performed by residents who completed a surgical curriculum safely and effectively reduced corneal astigmatism, regardless of meridian and amount, with refractive and keratometric efficacy for at least 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In their study, the horizontal incision caused corneal astigmatism to increase from 1.16 D at 90.5°to 1.45 D at 90.2°, while the manifest astigmatism decreased from 0.93 D at 93.2°to 0.72 D at 87.4°. They [17]. Compared with onaxis incision, the level of astigmatism reduction achieved at the intended meridian was significantly more favorable with the LRI technique [18].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In their study, the horizontal incision caused corneal astigmatism to increase from 1.16 D at 90.5°to 1.45 D at 90.2°, while the manifest astigmatism decreased from 0.93 D at 93.2°to 0.72 D at 87.4°. They [17]. Compared with onaxis incision, the level of astigmatism reduction achieved at the intended meridian was significantly more favorable with the LRI technique [18].…”
Section: Discussionmentioning
confidence: 95%
“…Riaz et al. demonstrated that LRI during cataract surgery achieved an effective and sustained reduction of both refractive and keratometric astigmatism, regardless of the meridian or magnitude of astigmatism; this correction persisted for at least 1 year postoperatively [ 17 ]. Compared with on-axis incision, the level of astigmatism reduction achieved at the intended meridian was significantly more favorable with the LRI technique [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether the direction of the CSC in uences astigmatism correction or anterior corneal high-order aberration (HOA) requires veri cation. As far as we know, studies [9][10][11] have reported the refractive and keratometric outcomes of limbal relaxing incisions during cataract surgery, whereas few studies have investigated the in uence of the location of the CSC on the refractive and optical outcomes after SMILE. We directed this randomized review to analyze the refractive and corneal optical quality results between two CSCs in SMILE surgery.…”
Section: Introductionmentioning
confidence: 99%
“…
Comment on: Refractive and keratometric outcomes of supervised novice surgeon performed limbal relaxing incisions We read with great interest the article by Riaz et al 1 The authors evaluated the efficacy and safety of astigmatism management using limbal-relaxing incisions performed by refractive surgeons in training. This study provides a reference for the performance of systematic astigmatism incisions in cataract surgery patients by ophthalmology residents.
…”
mentioning
confidence: 99%
“…2,3 Both the Journal of Refractive Surgery and the Journal of Cataract & Refractive Surgery suggest using the Alpins method together with the recommendations of Abulafia et al 3–5 In the study by Riaz et al, although Alpins terminology is used to discuss astigmatism outcomes, the term surgically induced astigmatism (SIA) does not accurately reflect Alpins' original term. 1 Alpins defines the SIA as the amount and direction of corneal steepening that occurred in achieving the operative result from the preoperative astigmatic state. 6 Consequently, the SIA vector could take any orientation as it does not depend directly on the target-induced astigmatism (TIA) meridian.…”
mentioning
confidence: 99%